'Today and more than ever, I FEEL LIKE A RESEARCHER': successful online learning collaborations between librarians and a Graduate School. (25th April 2014) - Newall, Elizabeth; Gratton, Christine; Maltby, Jane
Abstract This article describes the development and delivery of an online module at the University of Nottingham on the literature review process. In particular, it discusses how academic librarians collaborated with researcher developers at the Graduate School at the University to deliver a highly successful online learning experience for students. The article provides an overview of the course, a discussion on the experiences of both the tutors and participants involved, concentrating specifically on those in Medicine and Health Sciences. Details about future international collaborations and development of the course are also provided.